Conversational interfaces and the Web - Ripa, Gonzalo (2022)
Conversational User Interfaces (CUI), both in voice interaction and chatbot ways, have become an important and popular way of interacting with current applications. These kinds of interfaces are nowadays spreading around the Web for multiple purposes, although the vast majority of Web sites do not provide them yet. There is still a huge gap between what Web applications allow users to do via Graphical User Interfaces (GUI), and what CUI offers. Also, there are unanswered questions about CUI design and its usability impacts on web browsing. Although other approaches for CUIs creation, the proposed approach transfers the responsibility of creating the conversational interfaces to the users of the Web browser, instead of remaining an implementation decision taken by the Web site owners. In this sense, an End-User Development (EUD) environment was designed to allow end users to define conversational interfaces by themself, based on annotations of UI elements from Web Sites. In the case of Chatbots, plugged into the target Web sites, and in the case of Voice Interfaces (VUI), creating applications for smart speakers’ devices based on third-party Web sites content. The underlying ideas and the reference architecture could be used to create tools that allow fast prototyping of CUIs, which could be important to conduct exploratory studies about the impact of using them in Web applications.